2016
DOI: 10.3892/or.2016.4708
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-194 restrains the cell progression of non-small cell lung cancer by targeting human nuclear distribution protein C

Abstract: NSCLC accounts for over 80% of all lung cancers and is associated with poor prognosis. Human nuclear distribution C (hNUDC) was predicted to be the target gene of microRNA-194 (miR-194). The present study was designed to demonstrate the mechanism of miR-194 in the regulation of non-small cell lung cancer (NSCLC) via targeting the hNUDC. The hNUDC expression was found to strongly be increased while the miR-194 decreased significantly in the NSCLC cell lines when compared with the healthy controls. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Currently, there are few studies on the role and underlying mechanism of miR-194 in NSCLC. Zhou et al found that there is relatively low expression of miR-194 in NSCLC patients [20]. After the restoration of miR-194 level in vitro, the proliferation of tumor cells was inhibited, suggesting that the anti-tumor effect of miR-194 may be through the inhibition of its target gene hNUDC [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are few studies on the role and underlying mechanism of miR-194 in NSCLC. Zhou et al found that there is relatively low expression of miR-194 in NSCLC patients [20]. After the restoration of miR-194 level in vitro, the proliferation of tumor cells was inhibited, suggesting that the anti-tumor effect of miR-194 may be through the inhibition of its target gene hNUDC [20].…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al found that there is relatively low expression of miR-194 in NSCLC patients [20]. After the restoration of miR-194 level in vitro, the proliferation of tumor cells was inhibited, suggesting that the anti-tumor effect of miR-194 may be through the inhibition of its target gene hNUDC [20]. However, due to small sample size, multiple downstream targets and complex regulation network of microRNAs, more studies were warranted to validate the possible target genes of miR-194 and reveal its role in the development of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…miR-194 can inhibit colorectal carcinogenesis by targeting mitogen-activated protein kinase 4 (37) or Akt2 (31). Several studies have reported that miR-194 represses the progression and metastasis of non-small lung cancer through targeting bone morphogenetic protein 1 and p27 kip1 (38), forkhead box A1 protein (39) and human nuclear distribution protein C (29). miR-194 can suppress gastric cancer cell proliferation and EMT through targeting RING box protein 1 (40) and forkhead box protein M1 (41).…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has suggested that miR-194 functions as a tumor suppressor in many types of human cancers including lung cancer (29), hepatocellular carcinoma (30) and colorectal cancer (31). However, the role of miR-194 in glioma remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a family of small non-coding RNAs, are processed from precursor RNAs with a typical hairpin secondary structure (8). Several miRNAs are aberrantly expressed in NSCLC and their dysregulation has resulted in cancer progression and poor clinical outcome (9)(10)(11). Considering that miRNAs usually act as EMT-associated downstream effectors of receptor signaling or protein kinases (12), miRNAs may represent novel targets for designing antimetastatic drugs due to their specificity.…”
Section: Introductionmentioning
confidence: 99%